2020
DOI: 10.1108/lm-12-2019-0087
|View full text |Cite
|
Sign up to set email alerts
|

Environmental education in libraries – theoretical foundations and practical implementation

Abstract: PurposeThe purpose of this paper is to explain the concepts related to environmental education in the context of sustainable development, to indicate the links between them as well as to identify and organize elements of library activities that have the potential to implement environmental education.Design/methodology/approachThe method of analysis and criticism of scientific and professional literature and research reports was used. The multiple case study method was also used.FindingsAn analysis of literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…, 2016), to clarify the terminology (Fourie, 2012; Sahavirta, 2017, 2018; Fedorowicz-Kruszewska, 2020b), to adopt indicators for green libraries (Cardoso and Machado, 2017) and to identify new (also in terms of nomenclature) research areas, such as green information literacy (Kurbanoğlu and Boustany, 2014), ecological libraries, ecological library science (Víquez et al. , 2015) and environmental education in libraries (Fedorowicz-Kruszewska 2020a). Therefore, theoretical foundations of this sub-discipline of library science, focusing on green libraries, began to emerge.…”
Section: Resultsmentioning
confidence: 99%
“…, 2016), to clarify the terminology (Fourie, 2012; Sahavirta, 2017, 2018; Fedorowicz-Kruszewska, 2020b), to adopt indicators for green libraries (Cardoso and Machado, 2017) and to identify new (also in terms of nomenclature) research areas, such as green information literacy (Kurbanoğlu and Boustany, 2014), ecological libraries, ecological library science (Víquez et al. , 2015) and environmental education in libraries (Fedorowicz-Kruszewska 2020a). Therefore, theoretical foundations of this sub-discipline of library science, focusing on green libraries, began to emerge.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that librarianship is a set of skills and activities that are necessary to manage library resources and services, and to perform other tasks assigned to libraries, ‘green librarianship’ should be defined as a set of skills and activities that are necessary to achieve a library’s objective, which is environmental sustainability. To achieve this objective, the environmental literacy of library employees, its users and more broadly the local community, which can be achieved through environmental education, is necessary (Fedorowicz-Kruszewska, 2020). The proposed definition is general enough to cover all the designations of this concept, including those not yet identified.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the publications with a holistic usage and understanding of the core concepts cover the same research topics identified from reviewing the environmental, economic, social and cultural publications. Here, we find a focus on "sustainable libraries" in terms of buildings, practices and services (see Hauke, 2018;Fedorowicz-Kruszewska, 2019, 2020a; JD 78,6 on library advocacy, image and marketing (see Jankowska et al, 2014;Williams et al, 2015); on library development and strategies (see Hildreth and Sullivan, 2015;Granda and Machin-Mastromatteo, 2016). Moreover, we find research literature addressing issues of access and accessibility (Kosciejew, 2020) and community development (Li et al, 2019).…”
Section: Libraries and Sustainability: A Reviewmentioning
confidence: 99%